Looking further! The importance of embedding visual search in action. (2017) - van der Kamp, John; Dicks, Matt
Abstract: A unified account of visual search in complex everyday environments requires additional deliberations on the functional grounding of Hulleman & Olivers' (H&O's) functional viewing field (FVF) model. Their model can accommodate exploitation of information that is distributed across the immediate environment. Yet the differences in search between genuinely interacting in the environment and merely watching it should challenge researchers to look further.